2010
DOI: 10.1007/s11249-010-9609-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Nitriding Environment and Time on Plain Fatigue and Fretting Fatigue Behavior of Ti–6Al–4V

Abstract: Plasma nitriding was performed on Ti-6Al-4V fatigue test samples at 520°C in two environments (nitrogen and nitrogen-hydrogen mixture in a ratio of 3:1) for two time periods (4 and 18 h). Plain fatigue and fretting fatigue tests were conducted on unnitrided and plasma nitrided samples. Plasma nitriding degraded lives under both plain fatigue and fretting fatigue loadings. The samples nitrided in nitrogen exhibited superior lives compared with the samples nitrided in the nitrogen-hydrogen mixture, possibly due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…The layers under the compound layer were an Al-rich layer and an α-case which were created when Ti and N were formed on the compound layer, [27,41]. However, the main focus of this research section was on the compound layer thickness and α-case as both properties could possibly reduce the bending fatigue strength due to high hardness with low toughness [22][23][24][25]. The lowest time and temperature of the plasma-nitriding On the other hand, focusing on the compound layer in Figure 6, the pictures of the microstructure in the cross-section on the near-surface in different plasma-nitriding conditions are subsequently illustrated in Figure 7.…”
Section: Microstructure Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The layers under the compound layer were an Al-rich layer and an α-case which were created when Ti and N were formed on the compound layer, [27,41]. However, the main focus of this research section was on the compound layer thickness and α-case as both properties could possibly reduce the bending fatigue strength due to high hardness with low toughness [22][23][24][25]. The lowest time and temperature of the plasma-nitriding On the other hand, focusing on the compound layer in Figure 6, the pictures of the microstructure in the cross-section on the near-surface in different plasma-nitriding conditions are subsequently illustrated in Figure 7.…”
Section: Microstructure Analysismentioning
confidence: 99%
“…However, there is a problem found when applying the nitriding process to Ti-6Al-4V. The compound layers of nitrided Ti-6Al-4V, which are δ-TiN, Ti 2 N, and α-case, are found with high hardness after higher temperatures, resulting in lower toughness which leads to a decrease in bending fatigue strength [22][23][24][25]. In addition, it is found that the temperature required for the nitriding of Ti-6Al4V is higher than those of steel alloys which is not over 550 • C due to the higher hardness of diffusion [22], which would increase the thickness of the compound layer [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 shows the ratio of the average fatigue life obtained with the specimens with shot peening over the average life obtained with the specimens without any treatment versus fatigue life without shot peening. For finite lives between 10 4 and 10 5 cycles, the fatigue-life improvement ratio ranges between 3 and 15, which is much better than that observed with other types of surface treatment, such as nitriding (ranging from a negative effect to an improvement in fretting fatigue life of about 70%) [11,[47][48][49] or carburizing, which has a negative effect [50]. There is some scatter in this graph, but given the wide range and combination of loads, it seems that there is a strong relation between fatigue life and the fatigue-improvement ratio.…”
Section: Shot-peening Improvement Of Fatigue Lifementioning
confidence: 99%
“…Further, in order to improve performance, some surface treatments are used to expand the scope of application and extend the service life. Many nitrogen-based surface modifications have been used to improve the wear performance of the titanium alloy by increasing the surface hardness and consequently improving the sliding wear resistance [3]. Plasma nitriding treatment is widely used because this technology can produce TiN coating which has good corrosion resistance and beautiful appearance.…”
Section: Introductionmentioning
confidence: 99%